Microfluidic deformability analysis of the red cell storage lesion. Issue 15 (26th November 2015) - Matthews, Kerryn; Myrand-Lapierre, Marie-Eve; Ang, Richard R.; Duffy, Simon P.; Scott, Mark D.; Ma, Hongshen
Abstract: A key challenge in transfusion medicine research and clinical hematology is to develop a simple and non-destructive method to measure the quality of each blood unit prior to use. RBC deformability has long been proposed as an indicator of blood quality. We measured RBC deformability using the pressure required for single cells to transit through a micrometer scale constriction to examine longitudinal changes in RBC deformability, as well as the variability in blood quality and storage capacity across donors. We used a microfluidic device to monitor deformability changes in RBCs stored in plastic tubes and in blood bags over 14 and 56 days respectively. We found consistent storage based degradation of RBC deformability with statistically significant variability in both the initial RBC deformability and storage capacity among donors. Furthermore, all samples exhibited a transient recovery phenomenon. Deformability profiling of stored RBCs using transiting pressure showed significant donor variability in initial quality and storage capacity. This measurement approach shows promise as a rapid method to individually assess the quality of stored RBC units.